2020
DOI: 10.3727/152599519x15506259856480
|View full text |Cite
|
Sign up to set email alerts
|

Community Events: Committees, Challenges, And Cooperation

Abstract: Despite the growing interest in community–led organisations there remains some events operated by not–for–profit organisations that have not been fully explored. Even when there is a significant socio–cultural contribution to the host communities. Although this study is set within Highland Games there are many similarities to many not–for–profit event organisations managing traditional community events or cultural celebrations such as Hogmanay or Common Ridings. The challenges facing volunteer organisations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…This aligns with previous studies which found first-hand experiences and collective consumption of experiences are necessary to foster place attachment and place identity (Davis, 2016). Across all focus groups, participants identified pro-social motivations for hosting events, reinforcing that community events do not prioritise revenue generation and instead mostly generate income to support the ongoing operation of the event itself (Brewster, 2020). As highlighted in the focus groups, being involved in organisation of an event for communities to build more connected places is attractive to local residents:…”
Section: Community Events As Place-builderssupporting
confidence: 86%
See 4 more Smart Citations
“…This aligns with previous studies which found first-hand experiences and collective consumption of experiences are necessary to foster place attachment and place identity (Davis, 2016). Across all focus groups, participants identified pro-social motivations for hosting events, reinforcing that community events do not prioritise revenue generation and instead mostly generate income to support the ongoing operation of the event itself (Brewster, 2020). As highlighted in the focus groups, being involved in organisation of an event for communities to build more connected places is attractive to local residents:…”
Section: Community Events As Place-builderssupporting
confidence: 86%
“…This aligns with previous studies which found first-hand experiences and collective consumption of experiences are necessary to foster place attachment and place identity (Davis, 2016). Across all focus groups, participants identified pro-social motivations for hosting events, reinforcing that community events do not prioritise revenue generation and instead mostly generate income to support the ongoing operation of the event itself (Brewster, 2020). As highlighted in the focus groups, being involved in organisation of an event for communities to build more connected places is attractive to local residents:It’s the community that’s going to be doing this, it’s me, it’s my neighbour, it’s my father, my brother, my sister and it installs that whole aspect of ‘this is an event that going to be organized not just for me but for my neighbours and the wider community and I want to be a part of that' (EC1_FG)…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations